Ego Is the enemy : The fight to Master our greatest opponent - Holiday, Ryan (New York : Portfolio, 2017)
In the tradition of Steven Pressfield's The War of Art, a short, powerful meditation on ego and creativity, from the bestselling author of The Obstacle is the Way. In The Obstacle is the Way, Ryan Holiday introduced tens of thousands of readers to the world of Stoic philosophy. In The Ego is the Enemy, Holiday again delivers practical and inspiring philosophy to people who need it, picking up on a powerful concept that runs back centuries, across borders and schools of thought. Our main impediment in life is not the outside world but ourselves. It's our ego that is our most common enemy. Early in our careers, it can prevent us from learning and developing our talents. When we taste success, ego can blind us to our own faults, alienate us from others and lead to our downfall. In failure, ego is devastating and makes recovery all the more difficult. It is only by identifying our ego, speaking to its desires, and systematically disarming it that we will ever create our best work. In The Ego is the Enemy, Holidaydraws on a vast array of stories and examples, from literature to philosophy to history to his own experience advising many high-profile clients. Like Steven Pressfield's The War of Art, the book offers a brutally honest portrait of how we let our egos seduce us, and offers valuable advice for how we can overcome them.
Part I. Aspire -- Talk, talk, talk -- To be or to do? -- Become a student -- Don't be passionate -- Follow the canvas strategy -- Restrain yourself -- Get out of your own head -- The danger of early pride -- Work, work, work -- For everything that comes next, ego is the enemy... -- Part II. Success -- Always stay a student -- Don't tell yourself a story -- What's important to you? -- Entitlement, control, and paranoia -- Managing yourself -- Beware the disease of me -- Meditate on the immensity -- Maintain your sobriety -- For what often comes next, ego is the enemy... -- Part III. Failure -- Alive time or dead time? -- The effort is enough -- Fight club moments -- Draw the line -- Maintain your own scorecard -- Always love -- For everything that comes next, ego is the enemy...
Includes bibliographical references (pages 221-224).
Title from resource description page (Recorded Books, viewed September 28, 2015).
Keywords: Egoism; Ambition; Success; Conduct of life; Electronic books